Perilaku Kerja Proaktif dalam Pengembangan UMKM - Arlindo do Ceu Fatima; Imam Muklhlis; Arief Noviarakhman Zagladi (Universitas Batanghari Jambi, 2023)
The objective of this research is to find out the effects of Proactive Working Behavior on the growth of Â MSMEs, to analyze the factors that drive or hinder Proactive Works in MSMEs, to provide guidance and recommendations through the contribution to knowledge and scientific literature, and to measure the social and economic impact. Primary data collection is done through observation or observation. Secondary data is collected from scientific literature and research journals related to proactive behavior in developing Â MSMEs. The method approach used to make conceptual is the qualitative approach to postpositivism and positivism with the degree of belief that there is a reality that happens to depend on our thinking that can be studied through scientific methods. Critical realism, however, acknowledges that the theory can be modified through proactive behavior in developing Â MSMEs.